OPTIMIZING THE ROLE OF THE BINMAS UNIT THROUGH GUIDANCE AND COUNSELING IN PREVENTING THE CRIME OF MOTOR VEHICLE THEFT IN THE JEPARA POLICE STATION - REDIKA ADITYA SILALAHI (Indonesian Journal of Police Studies, 2022)
OPTIMIZING THE ROLE OF THE BINMAS UNIT THROUGH GUIDANCE AND COUNSELING IN PREVENTING THE CRIME OF MOTOR VEHICLE THEFT IN THE JEPARA POLICE STATION REDIKA ADYTIA SILALAHI, redikasilalahi@gmail.com Crime is behavior or action that causes loss of order or balance to other people. One form of crime is conventional crime, namely crimes against the soul, body, property, objects and psyche in the usual way or in new dimensions. An example of a conventional crime is motor vehicle theft. And the crime of motor vehicle theft in Indonesia is still relatively high with a comparison of one in 4,923 vehicles having the potential to be stolen or lost. This certainly needs special attention for the National Police as the institution responsible for public security and order. In this case the function of Binmas which is one of the functions that carry out the function of prevention has a role to provide knowledge to the public about preventing the crime of motor vehicle theft through guidance and counseling activities. At the Jepara Police, the crime of motor vehicle theft has always been one of the highest crimes every year. In this paper, the author uses the theory of management functions by George R. Terry, namely POAC to answer the first problem which consists of planning, organizing, implementing and supervising. The theory of management functions is used to answer the first problem formulation. The second theory used to answer the two problems is the management elements consisting of Man, Money, Method, Material, and Machine. The findings at the time the research was conducted, based on the POAC theory, it was found that there were still shortcomings in terms of planning. It is proven from the activity plan which does not have clear details regarding the activities, goals and targets to be achieved. Making an activity plan is only a formality. In addition, the organization is constrained by the limited number of members so that it involves other units in the implementation of guidance and counseling. At the implementation stage there are also constraints because it is still in the COVID-19 pandemic. The efforts of Satbinmas are still not optimal, so the authors suggest that in terms of lack of personnel, Satbinmas can cooperate with other parties such as the TNI and Lurah in the implementation of guidance and counseling. And the Zoom Meeting method as a means of implementing guidance and counseling during the COVID-19 pandemic that is still sweeping the world